Neo-militant Democracy and (Un)fulfilled Destination of Consolidated Democracies? The Inner Six in Comparative Perspective - Rak, Joanna (Historia i Polityka, 2022)
Drawing upon the methods of qualitative source analysis and process tracing, the study addresses the following research questions: How was the national legislation of consolidated democracies positioned to neo-militant democracy measures during the recovery from the great financial crisis (2007–2009)? To what extent was democracy prone to authoritarian abuse depending on a neo-militant democracy rule implementation? It advances arguments to reject Carlo Invernizzi Accetti’s and Ian Zuckerman’s hypothesis that if the freedom of political actors is restricted through militant democracy measures, democracy becomes more prone to authoritarian abuse in the long run. In the founding states of the EU, neo-militant democracy measures functioned in the legal structures long before the outbreak of the great financial crisis, during the crisis (2007–2009), and in the period of recovery. The states restricted democratic freedoms of speech, the press, association, and assembly. Belgium, Luxembourg, and Germany also limited organization in political parties. Moreover, during the recovery from the crisis, that is, a period of particular vulnerability of democracy to authoritarian abuse, the lists of relevant precautions were extended in France, Italy, and Germany. In these states, strengthening neo-militant democracy measures was neither a factor undermining democracy nor making it prone to drift towards a hybrid or authoritarian regime.